Molecular characterization of blaESBL–harboring conjugative plasmids identified in multi-drug resistant Escherichia coli isolated from food-producing animals and healthy humans - Wang, Juan; Stephan, Roger; Karczmarczyk, Maria; Yan, Qiongqiong; Hächler, Herbert; Fanning, Seamus (Frontiers in Microbiology, 2013)
Background: Extended-spectrum β-lactamse (ESBL)-encoding genes are frequently mapped to plasmids, yet few of these structures have been characterized at the molecular level, to date. Methods: Eighty-seven ESBL-producing E. coli were isolated from fecal samples of food-producing animals and healthy humans in Switzerland from 2009 to 2011. Plasmid DNA of all isolates was purified. Broth mating assays were carried out individually for 32 isolates to determine if the ESBL marker could be transferred by conjugation. The plasmid sizes were determined by S1 nuclease pulsed-field gel electrophoresis (PFGE) and the plasmids were typed by PCR-based replicon typing. Susceptibility tests by disk diffusion followed with a re-analysis S1-nuclease PFGE and PCR reactions were performed to confirm plasmid transfer. Microarray was performed to detect additional antibiotic resistance markers and multi-locus sequence typing (MLST) was also performed in selected donor strains. The phylotypes were identified by triplex PCR. Results: About half (n=46) of the 87 isolates carried small (< 20-kb) plasmids. All selected 32 isolates contained large plasmids (ranging in sizes from 20- to 600-kb). Eleven plasmid replicon types were detected. Of these, IncFIA (n=5), IncFIB (n=9) and IncK/B (n=4) were common. Nine isolates demonstrated the ability to transfer their cefotaxime resistance marker at high transfer rates. Plasmid profile re-analysis of these transconjugants identified 16 plasmids. IncFIB and IncI1 were the most prevalent replicon types. Phylogenetic grouping showed that five of the nine donor strains belonged to phylogroup B1. Nine different STs were identified in nine tested donor strains. Conclusions: Characterization of these ESBL-encoding conjugative plasmids extends our understanding on these resistance markers in multi-drug resistant E. coli cultured from healthy human and animal sources.